2016
DOI: 10.1037/hea0000325
|View full text |Cite
|
Sign up to set email alerts
|

Self-control, daily negative affect, and blood glucose control in adolescents with Type 1 diabetes.

Abstract: Objective For adolescents with type 1 diabetes, maintaining optimal daily blood glucose control is a complex self-regulatory process that likely requires self-control. This study examined whether higher self-control was associated with lower daily negative affect about diabetes and, in turn, better daily blood glucose control, i.e., lower mean daily blood glucose (MBG) and smaller standard deviations of daily blood glucose (SDBG), through two paths: 1) self-control maintaining lower mean level of negative affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…But, to our knowledge, only one investigation studied both variability in negative affect and variability in glucose in the same study (30). Lansing et al (2016; 30) followed n=180 adolescents with type 1 diabetes for 14 days during which they completed diaries of negative affect and used a glucometer.…”
Section: Discussionmentioning
confidence: 99%
“…But, to our knowledge, only one investigation studied both variability in negative affect and variability in glucose in the same study (30). Lansing et al (2016; 30) followed n=180 adolescents with type 1 diabetes for 14 days during which they completed diaries of negative affect and used a glucometer.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents with better self-control capacity, i.e., the ability to modulate behavior, emotion, and cognition toward a goal (Finkenauer, Engels, & Baumeister, 2005), engage more frequently in adherence behaviors and experience better metabolic control (Berg et al, 2014; Hughes, Berg, & Wiebe, 2012; King et al, 2012; Lansing & Berg, 2014; Lansing, Berg, Butner, & Wiebe, 2016). However, there is increasing recognition that self-control is both an individual and interpersonal process.…”
mentioning
confidence: 99%
“…Adolescent self-control is also associated with better metabolic control, as indexed by glycosylated hemoglobin (HbA1c) percentages, as well as averages and variability in daily blood glucose levels (Berg et al, 2014; Lansing & Berg, 2014). The importance of self-control for understanding diabetes management is highlighted by findings that self-control predicts daily negative affect toward diabetes management and, in turn, daily blood glucose levels (Lansing, Berg, Butner, & Wiebe, 2016) and that high levels of self-control may buffer against worsening metabolic control over time (King et al, 2012). …”
mentioning
confidence: 99%
“…Finally, previous research has demonstrated that having a more balanced time perspective is associated with greater self-control ability [25]. Furthermore, greater selfcontrol ability has been found to be associated with better glycaemic control in adolescents with type 1 diabetes [26]. Therefore, there may be an indirect relationship between balanced time perspective and blood glucose monitoring via self-control ability.…”
Section: Why Might a Balanced Time Perspective Be Associated With Blomentioning
confidence: 90%
“…Trait self-control was assessed using the 13-item Brief Self-Control Scale (BSCS; [30]). Previous studies have demonstrated that the BSCS is a valid measure of self-control [e.g., 30] and it has been found to be associated with glycaemic control in individuals with type 1 diabetes [26]. Example items include: "I am good at resisting temptation" and "I often act without thinking through all the alternatives".…”
Section: Self-controlmentioning
confidence: 99%